2017
DOI: 10.2196/mhealth.8230
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Available Smartphone Apps to Support Postoperative Pain Self-Management: Scoping Review

Abstract: BackgroundRecently, the use of smartphones to deliver health-related content has experienced rapid growth, with more than 165,000 mobile health (mHealth) apps currently available in the digital marketplace. With 3 out of 4 Canadians currently owning a smartphone, mHealth apps offer opportunities to deliver accessible health-related knowledge and support. Many individuals experience pain after surgery, which can negatively impact their health-related quality of life, including sleep, emotional, and social funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 32 publications
6
72
0
5
Order By: Relevance
“…This problem has not been improved since Rosser and Eccleston's study in 2011. A study that reviewed postoperative pain self-management apps in 2017 reported 50% HCP involvement (5/10 apps) [24]. This percentage is much higher than percentages reported in other studies since we believe development of this type of pain app requires specialized medical knowledge.…”
Section: Involvement Of Hcp and Patients In App Developmentmentioning
confidence: 74%
See 3 more Smart Citations
“…This problem has not been improved since Rosser and Eccleston's study in 2011. A study that reviewed postoperative pain self-management apps in 2017 reported 50% HCP involvement (5/10 apps) [24]. This percentage is much higher than percentages reported in other studies since we believe development of this type of pain app requires specialized medical knowledge.…”
Section: Involvement Of Hcp and Patients In App Developmentmentioning
confidence: 74%
“…To improve the usability of software, end-users -here patients with chronic pain -should be involved in software development. Only two studies (published in 2014 and 2017) were interested in the involvement of end-users and reported that they could not find any information about end-user involvement in pain apps and in postoperative pain self-management apps, respectively [17,24]. We found 7 apps (19%) involved end-users in development yet only in an ad-hoc way since we limited our study to pain apps with a pain diary function.…”
Section: Involvement Of Hcp and Patients In App Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings suggest that mHealth apps have the potential to perform several specific clinical tasks that are conventionally performed by a GP. Previous studies have reported the roles of mHealth apps for patients with specific clinical goals, such as pain selfmanagement and weight management [28,29]. Such mobile app functions may replace several GP tasks, for example, an app for diagnosis could help users make decisions regarding further treatment options, therefore potentially replacing a GP for this purpose.…”
Section: Discussionmentioning
confidence: 99%